A validation of abstracted dive profiles relayed via the Argos satellite system: a case study of a loggerhead turtle - Kishida, Narumi; Okuyama, Junichi; Arita, Mamiko; Kume, Natsuki; Fujita, Kento; Nishizawa, Hideaki; Torisawa, Shinsuke; Mitsunaga, Yasushi (Animal biotelemetry, 2022)
Satellite telemetry devices can record movement data of animals along with the environmental data. Such data are relayed remotely via satellite systems, but are constrained by the limited bandwidth availability. A satellite relay data logger (SRDL) that can abstract dive profiles and compress the data for transmission using a broken stick model (BSM) has been widely used in studies on dive behavior and physiology of marine animals. However, there is still uncertainty in the abstracted dive profiles. Here, we aimed to evaluate the certainty of abstracted dive profiles (via satellite communication) in terms of dive performance (dive depth, duration, and dive type) by comparing it with the actual dive data (from the retrieved tag) in a loggerhead turtle deployed with the SRDL throughout a 1.4-year foraging period. There was no significant difference in the maximum dive depth between the retrieved and satellite transmission data; however, there was a slight but significant difference in the dive duration. The dives from both datasets were classified into five types. Inconsistent dive classifications occurred in 1.7% of the data. There was no significant difference in the proportion of time spent diving between the retrieved and satellite transmission data for each type during the common recording period. In monthly scale comparisons, however, a significant difference was detected when the amount of data via satellite transmission was the smallest. Our results demonstrated that the dive data abstracted using BSM almost reconstructed the actual dive profiles with certainty in a loggerhead turtle, although slight inconsistencies were observed.